Surat Filipino traditional writing - Afable, Malu; Medina, Susan Calo (Travel Time, 1997)
Explore the indigenous systems of writing that have existed and continue to be in use in the islands of Mindoro and Palawan. Explore the ties that binds these systems to those which are no longer in use in our islands.